Colloquium Practical Applications of Instrumentation in the Mining and Metallurgical Industries (The Southern African Institute of Mining and Metallurgy)
COLLOQUIUM PRACTICAL APPLICATIONS OF INSTRUMENTATION IN THE MINING AND METALLURGICAL INDUSTRIES Rapporteur: J. Laschinger A colloquium and general meeting of the Institute held jointly with the Instrument and Control Society of Southern Africa at Kelvin House, Johannesburg on 18th October, 1972, had as its theme "Practical Applications of Instrumentation in the Mining and Metallurgical Industries" Dr J. P. Hugo (President) was in the chair and about 200 members and visitors were present.